STRATIFIKASI SOSIAL PETANI PADI DI DESA PEMATANG SIKEK KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - ", Karmila; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Emerge social stratification cause high appreciation about something by society. This research do in the Pematang Sikek village which traditional society the most appreciate is land. So, the peoples have wide land will occupy top stratum and people have a little or donâ€™t have a land will occupy under sratum. In order to, researcher do research about â€Social Stratification Rice Plant Farmers in The Pematang Sikek Village, Rimba Melintang Subdistrict, Rokan Hilir Regencyâ€, the purpose to understand who rice plant farmer in Pematang Sikek village be top stratum and under stratum. Then, analysing thing most appreciate other land and observe how relation social stratum. Population in the research is rice plant farmer stay in the Pematang Sikek village is 298 peoples. Sample applying random sampling technic, amount to 45 peoples. The methods to analysing data is descriptive quantitative. Technic removal data applying observation and guided interview with interview orientation. The result of research, have respondent in the top stratum around 37,8 % that majority respondent have self land with same wide or more than one hectare, income from product rice plant around one million rupiah by month, rice plant product by year around eight coma six ton, and respondent in the under social stratum around 62,2 % that majority respondent have a less land one hectare with income less one million rupiah by month or have rice plant product by year three coma three ton, and dominant occupy semi permanent house/simple. Beside land, something most appreciate in rice plan farmer society in the Pematang Sikek village is income. Social relation form interaction social process is interaction social asosiatif that cooperation inter stratum by activity community self-help and group farmer.Keyword: social stratification, rice plant, farmers.